DRAINAGE REDESIGNING OF MANYAR STREET USING THE LOG PEARSON III METHOD - Abiyan Wimar Denandra; Liu xiao laoshi (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
In metropolitan settings, the drainage system is crucial. Systems for drainage are designed to release water from hydrological cycles as well as wastewater from homes and public spaces. Effective drainage systems can stop flooding or standing water from interfering with people's daily activities and causing damage to road bodies. The project's objective was to determine the amount of water discharge that could pass through drainage lines to prevent flooding in those lines, which would allow researchers to determine the underlying causes of the flooding in the study area. There are some of the theories and methods used to analyze the study. In addition, the theories are aimed to obtain the direction and insight to support the existing data. The theories and literatures are collected from several ways such as books and journals related to the topic. Moreover, the supporting data are directed to facilitate all the processes required. The analysis shows that the planned rainfall intensity during the 10 years is 158,302mm with the 10-year time return. Moreover, the result from the existing drainage capacity has a maximum capacity of 1,68 m^3/s which can maintain the maximum planned discharge from the data 0,8952 m^3/s. Based on the topography map, the water from the Manyar street will be transferred to the nearby river located right in front of the street. During the rainy season, water will start to collect and settle at the road, and later the flood happens. There are some factors that affect the flooding of this area, trash, sedimentation, and the height differences of the road.